A new species of genus Gilliesia Peters & Edmunds from China (Ephemeroptera: Leptophlebiidae) - Zhou, Chang-Fa (Zootaxa, 2004)
Gilliesia pulchra n. sp., the second known species of the genus Gilliesia Peters and Edmunds, is described from male and female imagos collected in Southwestern China. The new species represents a new generic record for this country and extends the known distribution of the genus east across the Himalayan Mountains.